Plan de inversión para el mejoramiento de la rentabilidad de Disprowin S.A., cantón Quevedo, período 2014 – 2017 - Sernaqué Paz, Tyrone Joel (2015)
The present work have as a target to prepare a plan of for the improvement of the profitability of Disprowin S.A., in the canton Quevedo, period 2014 - 2017. For the development of the same one there were used the analytical-synthetic methods and the qualitative-quantitative methods. It broke of the information facilitated by Disprowin S.A., for the conclusion of the same one. Disprowin S.A. presents an inefficient distribution of the monetary resources, in such a way that it does not reflect a margin of favorable utility. By means of the making of the design of plan of investment it was possible to establish variables that they help to that the Company Disprowin S.A., could maximize its profitability which will allow him to be a company with many economic solvency. The results obtained, on having prepared the investment plan, expire with the main target it is which is to improve the profitability of the company, such it is so of an investment of $ 131.305,60 profitability of $92.260,12 will be obtained, at the end of period of investment (5 years), the investment capital will recover it at the age in 3 years, 6 months, 14 days, these results reflect the roads of the plan of investment, therefore it is advisable to bear it in mind for a future investment.